Formulation of a Flavor Enhancer Based on Milkfish and Shrimp Waste with Shiitake Mushroom Addition: An Organoleptic Assessment - Nugraha, Kristian Agung; Minantyo, Hari; Grasielda, Ivana; Hartadji, Caecillia; Poillot, Johanes Marco (Jurnal Penelitian Pariwisata, 2025)
The objective of this study was to evaluate the development of a natural seasoning made from milkfish meat, shiitake mushrooms, and shrimp waste, as well as to assess its organoleptic properties. The research was conducted in Surabaya. The seasoning was prepared by drying and processing each ingredient into powder form, which was then mixed with other spices in varying formulations containing 0%, 10%, 15%, and 20% shiitake mushroom powder. The final products were subjected to organoleptic evaluation using a 4-point Likert scale by untrained panelists, who assessed the color, aroma, taste, and texture. Data were analyzed using Analysis of Variance (ANOVA) to identify significant differences among the samples. The results indicated that the 20% shiitake mushroom formulation enhanced the umami flavor without significantly affecting the color and texture (p > 0.05). However, aroma and taste were significantly influenced by the formulation (p < 0.05). This shows that the addition of shiitake mushroom powder contributes to flavor enrichment without altering the product’s appearance. Therefore, the formulation shows potential as a natural and nutrient-rich alternative seasoning. Further research is recommended to improve the product’s texture and shelf-life, making it more suitable for commercial production and market acceptance. Keywords: milkfish, shiitake mushroom, shrimp waste, seasoning, organoleptic test.